FLASH with carbon ions: tumor control, normal tissue sparing, and distal metastasis in a mouse osteosarcoma model - Tinganelli, Walter; Weber, Uli; Puspitasari, Anggraeini; Simoniello, Palma; Abdollahi, Amir; Oppermann, Julius; Schuy, Christoph; Horst, Felix; Helm, Alexander; Fournier, Claudia; Durante, Marco (Radiotherapy and oncology, 2022)
The FLASH effect is a potential breakthrough in radiotherapy because ultra-high dose-rate irradiation can substantially widen the therapeutic window. While the normal tissue sparing at high doses and short irradiation times has been demonstrated with electrons, photons, and protons, so far evidence with heavy ions is limited to in vitro cell experiments. Here we present the first in vivo results with high-energy 12C-ions delivered at an ultra-high dose rate.
Gesehen am 06.12.2022